Proceso de atención nutricional en paciente masculino de 58 años de edad con insuficiencia renal y anemia ferropenica. - Zurita Jiménez, Marvin Francisco (2022)
Chronic kidney failure is associated with cardiovascular disease, high blood pressure, and diabetes, and is often fatal when accompanied by another chronic disease, and also increases the risk of cardiovascular disease and stroke. The objective of this clinical case was to improve the nutritional status of patients with renal failure and iron deficiency anemia through diet therapy. For a patient diagnosed with renal insufficiency of 5 years of evolution, the study collected relevant bibliographic data, data from her clinical history, complementary laboratory tests, evaluations of nutritional status and more. This data is used to determine a diagnosis to guide treatment. The results obtained over two months of treatment reported significant improvements in nutritional status in patients diagnosed with chronic renal failure and iron deficiency anemia at the time of nutritional counseling. This is achieved through dietary therapy based on your nutritional needs.